Caesarean section rates and indications in the Democratic Republic of the Congo: The case of Mbandaka City - Patrick Bongbanga Mundembe; Roger Mwimba Mbungu; Félicien Kandolo Tshimungu; Jules Moti Kangite; Jean Claude Efoloko Likulu; Guillin Boboko Bikoko; Monizi Mawunu; Jean-Paul Koto-Te-Nyiwa Ngbolua (Orapuh Journal)
Introduction Caesarean section (CS) is a medically appropriate intervention for managing complications during childbirth. However, the increasing number of both scheduled and emergency CS procedures has led to concerns about the potential overuse of this technique. This trend has contributed to growing mistrust within the community, particularly in areas where CS is frequently performed. It is essential to examine the rates and indications for caesarean sections to understand the factors contributing to this increase and to address the concerns surrounding its use.